Diagnostic significance of dysregulated miRNAs in T-cell malignancies and their metabolic roles - Mondal, Deepankar; Shinde, Sapnita; Paul, Souvik; Thakur, Suresh; Velu, GSK; Tiwari, Atul Kumar; Dixit, Vineeta; Amit, Ajay; Vishvakarma, Naveen Kumar; Shukla, Dhananjay (Frontiers in Oncology, 2023)
T-cell malignancy is a broad term used for a diverse group of disease subtypes representing dysfunctional malignant T-cells transformed at various stages of their clonal evolution. Despite having similar clinical manifestations mostly, these disease groups have different disease progression and diagnostic parameters. The effective diagnosis and prognosis of such diverse disease group demands testing of molecular entities that captures footprints of the disease physiology in its entirety. MicroRNAs (miRNAs) are a group of non-coding RNA molecules that regulate the expression of genes, and while doing so, leaves behind specific miRNA signatures corresponding to cellular expression status in an altered stage of a disease. Using miRNAs as a diagnostic tool is justified, as they can effectively distinguish expressional diversity between various tumors and within subtypes of T-cell malignancies. As global attention for cancer diagnosis is shifting towards liquid biopsy, diagnosis using miRNAs is more relevant in blood cancers than in solid tumors. We also lay forward diagnostic significance of miRNAs that are indicative of subtype, progression, severity, therapy response, and relapse. This review discusses potential use and the role of miRNAs, miRNA signatures or classifiers in diagnosis of major groups of T-cell malignancies like T-cell acute lymphoblastic lymphoma (T-ALL); peripheral T-cell lymphoma (PTCL); extranodal NK/T-cell lymphoma (ENKTCL) and cutaneous T-cell lymphoma (CTCL). The review also briefly discusses major diagnostic miRNAs having prominent metabolic roles in these malignancies to highlight their importance among other dysregulated miRNAs.